(NsOWREMENNYE PROBLEMY FIZI^ESKOJ GEOGRAFII (B:s [(NsBORNIK STATEJ(B] /s - (NgWOZDECKIJ(B, (NnIKOLAJ aNDREEWI^s; (NdXQKONOW(B, (Nk(B.(Nn(B.s; (NmOSKOWSKIJ GOSUDARSTWENNYJ UNIWERSITET IM(B. (Nm(B.(Nw(B. (NlOMONOSOWA(B.s (NgEOGRAFI^ESKIJ FAKULXTETs ((NmOSKWA (B:s (Nmgu(B,s, 1989)
(NbIBLIOGR(B. (NW KONCE ST(B.s
Keywords: (NfIZI^ESKAQ GEOGRAFIQs